The Impact of Using Technology (Technostress) with the Forward Chaining Method as a Decision Support System: The Impact of Using Technology (Technostress) with the Forward Chaining Method as a Decision Support System - Syamsul Rizal; Muhammad Wali (Institute of Computer Science (IOCS), 2020)
This research focuses on the development of intermittent use of computer intentions, namely behavioral intentions in the termination phase, in the context of software engineering lessons, at Akubank Nusantara and AMIK Indonesia which uses a curriculum with more practice than learning material and this shows a very important role . This study aims to build an expert system application using the forward chaining method as a tool to measure instructor level and student learning. With this application, it can help academics and the quality sector to predict problems as early as possible so that they can be addressed in enhancing further learning. Research data used for diagnosis are symptoms as well as technostress disorders and information handling solutions. This research succeeded in making an expert system design to diagnose the technostress level of instructor and student learning by applying the Forward chaining method and analyzing calculations IF THEN ELSE, so that the application can measure computer-based learning technology.